2017
DOI: 10.1037/xge0000293
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of group mind: “People in a group” have more mind than “a group of people”.

Abstract: Three studies examine how subtle shifts in framing can alter the mind perception of groups. Study 1 finds that people generally perceive groups to have less mind than individuals. However, Study 2 demonstrates that changing the framing of a group from "a group of people" to "people in a group," substantially increases mind perception-leading to comparable levels of mind between groups and individuals. Study 3 reveals that this change in framing influences people's sympathy for groups, an effect mediated by min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
131
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(152 citation statements)
references
References 42 publications
13
131
7
Order By: Relevance
“…The materials and procedure for the current study were identical to Study 1a except as noted. After seeing each face, participants responded to 8 items adapted from Gray and colleagues' (2007) items were selected because they were the four that loaded most strongly onto the agency and experience factors in the original work (Gray et al, 2007; see also Cooley, Payne, Cipolli, & Gray, 2017). In our data, agency and experience were positively correlated, r(45) = .41, p = .005.…”
Section: Methodsmentioning
confidence: 52%
“…The materials and procedure for the current study were identical to Study 1a except as noted. After seeing each face, participants responded to 8 items adapted from Gray and colleagues' (2007) items were selected because they were the four that loaded most strongly onto the agency and experience factors in the original work (Gray et al, 2007; see also Cooley, Payne, Cipolli, & Gray, 2017). In our data, agency and experience were positively correlated, r(45) = .41, p = .005.…”
Section: Methodsmentioning
confidence: 52%
“…After seeing each face, participants responded to 8 items adapted from Gray and colleagues' (2007) ; α = .97). These items were selected because they were the four that loaded most strongly onto the agency and experience factors in the original work (Gray et al, 2007; see also Cooley, Payne, Cipolli, & Gray, 2017). In our data, agency and experience were positively correlated, r(45) = .41, p = .005.…”
Section: Methodsmentioning
confidence: 76%
“…However, recent research has suggested that for‐profit companies may suffer from a selective disadvantage in eliciting sympathy as victims (Cooley et al, ; Rai & Diermeier, ). According to these streams of research, to feel sympathy for an actor, or to attribute blame to them, people must perceive the actor as having a mind (H. M. Gray, Gray, & Wegner, ; Waytz, Gray, Epley, & Wegner, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the kind of mind consumers ascribe to organizations differs from that which they ascribe to other human beings. In particular, while consumers are willing to ascribe agentic mental states to for‐profit companies, they tend not to ascribe experiential mental states to them (Cooley et al, ; Knobe & Prinz, ; Rai & Diermeier, ). This distinction is critical for moral judgment because whereas agentic mental states are necessary for eliciting anger following transgression, experiential mental states are necessary for eliciting sympathy following victimization (K. Gray & Wegner, ).…”
Section: Introductionmentioning
confidence: 99%